2003
DOI: 10.2223/jped.1109
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver agreement in the radiological diagnosis of lower respiratory tract infections in children

Abstract: Objective: To evaluate the inter-observer agreement of radiological diagnosis of lower respiratory tract infections in children. Methods: Chest X-rays from 60 children younger than 5 years of age were evaluated by three physicians: a pediatric radiologist (PR), a pediatric pulmonologist (PP) and an experienced emergency pediatrician (EP). All children had sought an emergency room due to acute respiratory infections with apparent lower respiratory tract involvement. Observers were blinded to the original diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…It is likely that the number of infants diagnosed with pneumonia was overestimated in our sample, because the limitations, difficulties, and contradictions in the diagnosis of acute infectious pulmonary diseases in children are extremely common in clinical practice. (18) However, the high percentage of infants who had respiratory infection with pulmonary impairment in this sample is still a cause of concern. According to the Brazilian National Ministry of Health, respiratory diseases were responsible for 34.5% of all hospital admissions of children less than one year of age nationwide in 2006.…”
Section: Discussionmentioning
confidence: 84%
“…It is likely that the number of infants diagnosed with pneumonia was overestimated in our sample, because the limitations, difficulties, and contradictions in the diagnosis of acute infectious pulmonary diseases in children are extremely common in clinical practice. (18) However, the high percentage of infants who had respiratory infection with pulmonary impairment in this sample is still a cause of concern. According to the Brazilian National Ministry of Health, respiratory diseases were responsible for 34.5% of all hospital admissions of children less than one year of age nationwide in 2006.…”
Section: Discussionmentioning
confidence: 84%
“…In this regard, Albaum et al 7 and Boersma et al 8 encountered very similar findings, including the poor interobserver agreement for the type of infiltrates (≤ 0.3) and presence or absence of air bronchogram (≤ 0.31), poor to moderate agreement for pleural effusion (≤ 0.46), and moderate to good for multilobar pneumonia (≤ 0.67) and location of infiltrates (≤ 0.77). Also, Sarria et al 11 and Venera et al 3 found poor to moderate agreement for the variables mentioned in pediatric populations.…”
Section: Discussionmentioning
confidence: 95%
“…Most of them have assessed the agreement, or the percentage of agreement, between radiologists, pulmonologists, pediatricians, internists, emergency department specialists, residents and medicine students, in both children 3,4,11,[13][14][15][16][17] and adults, [5][6][7][8]12,[18][19][20][21][22][23][24][25] and the association with the etiologic agent, 8,[15][16][17] clinical presentation and outcomes. 20,23 Several of these studies have also estimated sensitivity, specificity and predictive values of chest X-rays for the diagnostic of pneumonia, its etiology and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations